A Mendelian randomization study investigating causal links between gut microbiota or metabolites and chronic hepatitis B - Xing, Tongjing; Wang, Xuequan; He, Shanshan (Frontiers in Public Health, 2024)
Objective This study aimed to explore the potential causal relationship between the gut microbiota and/or its metabolites and the progression of chronic hepatitis B (CHB). Method The gut microbiota was used as the exposure factor. The training set exposure data were obtained from the China Nucleotide Sequence Archive (CNSA). Genome-wide association study (GWAS) data from Asia were used as the outcome variables. Outcome data for both the training and validation sets were sourced from the GWAS Catalog database. A dual-sample Mendelian randomization approach was used to analyze the causal relationships, with the inverse variance-weighted method serving as the main analytical strategy. Sensitivity analysis was conducted to assess the robustness of Mendelian randomization analysis results. Result In the training set database, analysis using the inverse variance-weighted method revealed a positive correlation between Fusobacterium varium and chronic hepatitis B [OR = 1.122, 95% CI (1.016, 1.240), p = 0.022]. Conversely, Veillonella parvula exhibited a negative correlation with chronic hepatitis B [OR = 0.917, 95% CI (0.852, 0.987), p = 0.021]. Sensitivity analysis revealed no evidence of pleiotropy and heterogeneity. No gut microbiota metabolites with a causal effect on chronic hepatitis B were identified. Additionally, no associations between the gut microbiota and the progression of chronic hepatitis B were found in the validation data from the European cohort. Conclusion This study suggests that F. varium may facilitate the progression of chronic hepatitis B, whereas V. parvula may impede it. No causal relationships between gut microbiota metabolites and chronic hepatitis B were established.